The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1007/bf02053934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trimebutine on colonic function in patients with chronic idiopathic constipation

Abstract: A double-blind crossover study on the effects of trimebutine on large bowel function was performed in 24 consecutive patients complaining of chronic idiopathic constipation. Their stool frequency, colonic transit time, and colonic electrical activity were measured. They were divided into a group of constipated patients with "normal" transit time (less than 40 hours) (n = 12) and another group of constipated patients with "delayed" transit time (more than 40 hours) (n = 12). The patients received trimebutine (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
1
9
0
4
Order By: Relevance
“…In a previous study, we have provided evidence that for the pharmacological treatment of patients with chronic idiopathic constipation, a physiological rather than a clinical selection must be made. 22 Similarly, the present study confirms this approach. In patients with myelomeningocele, the appraisal of lower gastrointestinal symptoms should be made physiologically rather than clinically.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, we have provided evidence that for the pharmacological treatment of patients with chronic idiopathic constipation, a physiological rather than a clinical selection must be made. 22 Similarly, the present study confirms this approach. In patients with myelomeningocele, the appraisal of lower gastrointestinal symptoms should be made physiologically rather than clinically.…”
Section: Discussionsupporting
confidence: 89%
“…Accelerated transit through the proximal colon is demonstrable in a subset of patients with diarrhoeapredominant irritable bowel syndrome; 111 proximal colonic transit in these patients may be slowed following therapy with the opioid receptor agonist, trimebu-tine. 103 The marked acceleration (6´normal) of proximal colonic transit in carcinoid diarrhoea is discussed below. 112 Myoelectric and phasic pressure measurements of the left side of the colon in patients with diarrhoeal disorders and diverticular disease have been extensively studied.…”
Section: Diarrhoeamentioning
confidence: 99%
“…These results suggest that trimebutine is more effective for the treatment of diarrhea than for constipation. It has been reported that colonic transit time was reduced only in patients with delayed colonic transit and was slightly increased in patients with normal colonic transit (31). Careful selection of patients is needed, though difficult, if trimebutine is to be prescribed for constipation.…”
Section: Discussionmentioning
confidence: 99%